2020
DOI: 10.1039/c9ra09657d
|View full text |Cite
|
Sign up to set email alerts
|

Methanol to aromatics: isolated zinc phosphate groups on HZSM-5 zeolite enhance BTX selectivity and catalytic stability

Abstract: HZSM-5 zeolite combined with unique zinc and phosphorus species, yields excellent selectivity (∼85%) to BTX (benzene, toluene, xylenes) in aromatic products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…A recent study reported that isolated zinc phosphate groups directly bonded to the channels of ZSM-5 zeolites enhance the selectivity and stability in the conversion of methanol to aromatics. Analysis by 31 P MAS NMR confirmed the preferential formation of zinc phosphate groups (3 ppm) and a complementary study by EXAFS also identified a Zn–P bond visible by a peak around 3.05 Å with the actual bond length of 3.28 Å and the absence of Zn–Zn bonding …”
Section: Nonmetalsmentioning
confidence: 75%
See 1 more Smart Citation
“…A recent study reported that isolated zinc phosphate groups directly bonded to the channels of ZSM-5 zeolites enhance the selectivity and stability in the conversion of methanol to aromatics. Analysis by 31 P MAS NMR confirmed the preferential formation of zinc phosphate groups (3 ppm) and a complementary study by EXAFS also identified a Zn–P bond visible by a peak around 3.05 Å with the actual bond length of 3.28 Å and the absence of Zn–Zn bonding …”
Section: Nonmetalsmentioning
confidence: 75%
“…Analysis by 31 P MAS NMR confirmed the preferential formation of zinc phosphate groups (3 ppm) and a complementary study by EXAFS also identified a Zn−P bond visible by a peak around 3.05 Å with the actual bond length of 3.28 Å and the absence of Zn−Zn bonding. 906 Phosphorus-doped materials, mainly mesoporous carbons and graphene with phosphorus contents up to approximately 3 at. %, have also been explored as metal-free catalysts.…”
Section: Phosphorusmentioning
confidence: 99%
“…Catalysts playing significant roles in hydrogenation in naphthalene structure and selective cracking of naphthalenic structures-which yields one-ring aromatic hydrocarbons with alkyl chains-achieve the hydrotreating (HDT) and hydrocracking (HCK) processes used in the synthesis of BTX. Another method of producing BTX is the MTA (methanol to aromatics) reaction, which has been made possible primarily by developing methanol generated from biomass, shale gas, and coal via the syngas route [68,69]. BTX synthesis from syngas can reach good selectivity using a dual bed of MnCrOx-ZSM-512-MR zeolites.…”
Section: Production Of Benzene Toluene and Xylene (Btx) Aromaticsmentioning
confidence: 99%
“…By contrast, as reported in the literature, the addition of phosphorus species on HZSM-5 zeolites could effectively improve the catalyst stability and resistance to coke formation as compared with unmodified HZSM-5 zeolites. [3,33,34] In order to further improve the catalyst lifetime and BTX selectivity in the MTA reaction, nano-sized HZSM-5 zeolites modified by both ZnSiF 6 Á6H 2 O and phosphoric acid (Zn-P/HZSM-5) are prepared in this study. Moreover, nano-sized HZSM-5 zeolites modified by phosphoric acid (P/HZSM-5) with different molar concentrations are prepared as reference sample.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] By contrast, there is a surplus generation of methanol from coal mining. [ 3 ] In this context, the methanol to aromatics (MTA) reaction attracts the interest of industrial and academic researchers, which is considered a high‐efficiency nonpetroleum route to increase the production of BTX hydrocarbons by consuming excessive amounts of methanol.…”
Section: Introductionmentioning
confidence: 99%